Implementasi Metode Pembelajaran Peta Konsep pada Mata Pelajaran Sejarah Kebudayaan Islam di MA Sunan Ampel Pare - Duhaa Rohmawan (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2017)
The term learning is a term that we often encounter in everyday life. Every day as if - people will not be separated from learning activities. In general, learning is defined as a change in a person caused by experience. Islam is very appreciative and give appreciation and a high place for the people - knowledgeable people. It can be seen on the recognition and promise of Allah to the people who are studied in the Qur'an Surah Al Mujalah verse 11. The achievement of learning that can satisfy achieved by every student if they can learn fairly, avoid the various threats, obstacles, and disorders. But unfortunately, the threats, obstacles and disorders experienced by certain children So they have difficulty in learning. So it is important for a teacher to solve the problematics of students in learning. The key to success and success of a learner lies in a teacher, although it does not rule out the success of learning lies in the students themselves, as well as other aspects. To solve learning difficulties in students, the authors want to discuss about the concept of conceptual learning strategies, which according to the author is very appropriate to answer the problem of learning difficulties in students